PEMANFAATAN SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PEMETAAN RUMAH PENDUDUK DI RW 01/RT 02 KELURAHAN SEKARJAYA KECAMATAN BATURAJA TIMUR - Lucyana Lucyana (Jurnal Tekno Global, 2020)
Lack of data that contains information on people's houses also acts as an obstacle to the completion of the mapping of resident houses that is not spared from the importance of information in supporting all activities contained therein, the information generated must be relevant so that decisions made based on the information are right on target, the form of presentation according to is a factor that influences the quality of the information conveyed. So far the presentation of data and information in Kelurahan generally uses diagrams or graphs depending on what data you want to present.In utilizing the geographical information system for mapping population houses, the numbering and names of residents' houses have been adjusted. On this map, the addresses of residents of RW 01 / RT 02 KelurahanKelurahanSekar Jaya have been ordered. Based on the results of data processing, it was concluded that the Desktop-GIS that was built was able to display the mapping information of residents' houses in RT 02 / RW 01, Sekarjaya Village, East Baturaja District.Keyword : Geographic Information System, Sekarjaya Urban Village